solving quadratic equations by completing the square
in Algebra 2 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

2 Answers

x^2 -2x -5=0

become x-3.449489743)*(x+1.449489743)

quadratik equashun...

-b/2a=1, b^2-4ac=24, sqrt(24)=4.898979486, sqrt/21=2.4494897427831

x²-2x=5 ⇒ x²-2x+1=5+1 ⇒ x²-2x+1=6 ⇒

(x-1)²=6 ⇒ √(x-1)²=√6 ⇒ x-1=±√6 ⇒ x=1±√6

CK: x²-2x=(1+√6)²-2(1+√6)=(1+2√6+6)-2(1+√6)=5

x²-2x=(1-√6)²-2(1-√6)=(1-2√6+6)-2(1-√6)=5   CKD.

The answers are: x=1+√6, or x=1-√6


Related questions

Welcome to, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
84,531 questions
89,491 answers
11,942 users